Implementasi Profil Pelajar Pancasila dalam Pembelajaran PAI Kelas X di MAN 2 Gresik - Nurul Khomsatun; Moh. Solehuddin; Mulyadi Mulyadi (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2023)
This study aims to describe how to plan the implementation of the profile of Pancasila students in learning PAI Class X at MAN 2 Gresik, to describe how the implementation of the profile of Pancasila students in learning PAI Class X at MAN 2 Gresik, to describe how to evaluate the implementation of the profile of Pancasila students in learning PAI Class X at MAN 2 Gresik. The data analysis technique used in this study is data reduction, data presentation, and conclusion. The results of the research on the Implementation of Pancasila Student Profiles in Class X PAI Learning at MAN 2 Gresik include: 1) The process of compiling a Pancasila learning profile learning can be done by identifying learning objectives, learning materials, selecting learning methods, learning assessments, learning adjustments. 2) The implementation of Pancasila student profiles is carried out through several techniques, namely group discussions, giving individual assignments, simulations, techniques for using media, and group project techniques. 3) To measure the achievement of the Pancasila student profile at MAN 2 Gresik, it is carried out in several ways, namely written tests or oral tests that can be used to measure students' knowledge of Pancasila values ​​and their application in everyday life, observation and interviews, portfolios and self -assessment.